Needs Analysis in the designing of an EAP course for computer science graduate students - Vieira, Bruna Gabriela Augusto Marçal; Aranha, Solange (The ESPecialist, 2015)
This paper reports a needs analysis process to English for Academic Purposes courses, applied to Computer Science graduate students. The analysis aimed at determining both present and target situations in the use of the language, initially with 13, and after some modifications in the instrument, with 213 students. Results show, among other things, that a big part of the students have a positive view of their English language proficiency, revealing a need of tasks and approaches that consider such an image, in order to ensure bigger motivation and better performance of the students in the tasks of the course.